2018
DOI: 10.5194/hess-22-819-2018
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Using distributed temperature sensing for Bowen ratio evaporation measurements

Abstract: Abstract. Rapid improvements in the precision and spatial resolution of distributed temperature sensing (DTS) technology now allow its use in hydrological and atmospheric sciences. Introduced by Euser et al. (2014) is the use of DTS for measuring the Bowen ratio (BR-DTS), to estimate the sensible and latent heat flux. The Bowen ratio is derived from DTS-measured vertical profiles of the air temperature and wet-bulb temperature. However, in previous research the measured temperatures were not validated, and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 38 publications
(43 reference statements)
0
33
0
Order By: Relevance
“…The application of DTS is of great value to characterize thermal dynamics at a scale that corresponds to, for example, many geophysical processes. Heat tracer tests with DTS have been used to estimate wind speed [3,4], evaporation [5,6], soil moisture [7], groundwater-surface water interaction [1,8], and groundwater flow [9,10]. The specification sheets of DTS measurement systems list the uncertainty in the temperature estimated under ideal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The application of DTS is of great value to characterize thermal dynamics at a scale that corresponds to, for example, many geophysical processes. Heat tracer tests with DTS have been used to estimate wind speed [3,4], evaporation [5,6], soil moisture [7], groundwater-surface water interaction [1,8], and groundwater flow [9,10]. The specification sheets of DTS measurement systems list the uncertainty in the temperature estimated under ideal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…T was subsequently approximated as the difference between measured ET and the model for E soil during times when photosynthesis was active. Annual T / ET values from this approach varied from 0.35 to 0.66 in the grass ecosystem (US-Dk1) across a 4-year period and between 0.7 and 0.75 in the pine (US-Dk3) and hardwood (US-Dk2) forests, somewhat higher than global syntheses (Schlesinger and Jasechko, 2014), remote sensing estimates from PT-JPL (see Appendix A) for the Duke pine forest (Fig. 3), and sap-flow-based measurements from the deciduous forest (Oishi et al, 2008).…”
Section: Partitioning Et Using Half-hourly Eddy Covariance Observationsmentioning
confidence: 86%
“…(Wei et al, 2017). Other observational studies suggest that annual T / ET averages nearly 2/3 globally (0.61 ± 0.15, Schlesinger and Jasechko, 2014;0.64 ± 0.13, Good et al, 2015; and 0.66 ± 0.13 across some FLUXNET sites, Li et al, 2019). Intercomparison studies agree on the large uncertainty surrounding these estimates, with reported global terrestrial annual T / ET ratios ranging from 0.35 to 0.90 (Coenders-Gerrits et al, 2014;Fatichi and Pappas, 2017;Young-Robertson et al, 2018).…”
Section: Vegetation Plays a Central Role In Evaporation And Transpiramentioning
confidence: 93%
See 2 more Smart Citations